Efektifitas Senam Knee Chest Position Terhadap Kehamilan Sungsang Di Klinik Ar-Rahim Kec. Carenang Kab. Serang Banten - Masri Masri; Riza Faulina (Universitas Malahayati Lampung, 2024)
ABSTRACT Breech pregnancy causes a high risk of morbidity and mortality. Most breech pregnancies end in a Caesarean section. In a cephalic pregnancy, the head, which is the largest part of the fetus, is born first, whereas in a breech position, the largest part of the fetus is born last. Birth of the head in the breech position does not have a